Validity of the Expanded Levenson Self-Report Psychopathy (E-LSRP) in a Brazilian sample: factor structure, construct validity, and Associations with the Brazilian Jeitinho - Machado, Gisele Magarotto (Deviant behavior, 2025)
We aimed to adapt the Expanded Levenson Self-Report Psychopathy (E-LSRP) to the Brazilian context, evaluate its internal structure and construct validity. We also aimed to expand the psychopathy nomological network by providing information about E-LSRP factors’ associations with a Brazilian cultural phenomenon known as Brazilian Jeitinho. Our sample comprised 1,445 Brazilian adults, with ages varying from 18 to 81 years (M = 31.13; SD = 13.22). The participants completed the E-LSRP, as well as the Triarchic Psychopathy Measure, Crime and Analogous Behavior Scale, Affective and Cognitive Measure of Empathy, and Brazilian Jeitinho Questionnaire. Results showed general support for a three-factor structure, and that E-LSRP scores exhibited the expected associations with external criterion measures. Our results demonstrated that E-LSRP Egocentricity was the factor most related to Brazilian Jeitinho. Although we have initial validity evidence supporting the Brazilian version of E-LSRP, future studies need to replicate these findings in other samples.